The Idea of Memory in the Context of «the Secret Garden» by Frances Hodgson Burnett - Masliakova A. I. (Interactive science, 2022)
the importance of memory is difficult to underestimate. Not only does it help us to reinforce our cultural identity, but it also gives us an opportunity to learn from our mistakes and be more successful in the future. Yet some people tend to forget how precious and significant their memories are. And I do believe that it is high time we walked down memory lane and tried to set things right.
Keywords: память; история искусства; memory; путешествия; забывание; art history; культурная идентичность; forgetting; cultural identity; travelling